An unusual case of pseudochylothorax - M Padma Priya; S Dharmic; Aparajeet Kar; V Suryanarayana (Wolters Kluwer Medknow Publications, 2015)
A 25-year-old male patient presented with right-sided pleuritic chest pain and pain in the ankle. Radiological investigations revealed a right sided pleural effusion, lytic lesion in spine D10 with paravertebral abscess. Pleural fluid analysis showed elevated lactate dehydrogenase, adenosine deaminase, increased triglycerides, cholesterol, and no chylomicrons. Hence, a diagnosis of pseudochylothorax secondary to tuberculosis was made. Pleural fluid was drained by tube thoracostomy, decortication was done to improve the lung function and patient was started on anti-tuberculosis treatment (ATT). Patient improved with ATT. Pseudochylous effusion or chyliform effusions are uncommon. <200 cases has been reported in the international literature. The possibility of tuberculosis has to be considered in diagnosis and treatment of such cases. Here, we present a case of tuberculous pseudochylous effusion.